Cutting to measure the elasticity and fracture of soft gels. Issue 38 (7th September 2020) - Duncan, Teresa T.; Sarapas, Joel M.; Defante, Adrian P.; Beers, Kathryn L.; Chan, Edwin P.
Abstract : In this work, a razorblade-initiated fracture test (RIFT) is introduced that can measure the mechanical properties related to fracture for soft polymeric gels. Abstract : The fracture properties of very soft and/or brittle materials are challenging to measure directly due to the limitations of existing fracture testing methods. To address this issue, we introduce a razorblade-initiated fracture test (RIFT) to measure the mechanical properties related to fracture for soft polymeric gels. We use RIFT to quantify the elasticity, crack initiation energy, and the fracture energy of gellan hydrogels as a function of gellan concentration. Additionally, we use RIFT to study the role of friction in quantifying the fracture properties for poly(styrene- b -ethylene butadiene- b -styrene) gels as a function of test velocity. This new method provides a simple and efficient means to quantify the fracture properties of soft materials.